2012
DOI: 10.3918/jsicm.19.359
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of thrombomodulin-^|^alpha; on septic disseminated intravascular coagulation (DIC): a historical cohort study

Abstract: 要約: 【目的】 敗血症に合併する播種性血管内凝固症候群 (敗血症性 disseminated intravascular coagulation, 敗血症性 DIC) に対するトロンボモジュリンアルファ (thrombomodulin-α, TM-α) の治療効果を検討した。 【方法】 敗血症性 DIC 患者対象のヒストリカルコホート研究であり, TM-α群 (30 例) :全対象患者に TM-αを投与,non-TM-α群 (23 例) :全対象患者に TM-α投与 せず,とした。 【結果】 両群間で重症度に差はなかった。30 日生存率は,TM-α群 90.0% (27/30 例) に対して non-TM-α群 65.2% (15/23 例) であった (P = 0.041) 。抗 DIC 薬投与 7 日目の DIC 離脱率は,50.0% (15/30 例) vs. 34.8% (8/23 例) であった (P = 0.268) 。High mobility group box 1 の変化率は-48.1% (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…S2). The authors of eight of these studies were contac‐ted for further information about these changes. There was no difference between groups in the changes in FDP (mean difference, −11.7 μg mL −1 ; 95% CI, −32.9 to 9.5 μg mL −1 ; P = 0.28; I 2 = 32%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S2). The authors of eight of these studies were contac‐ted for further information about these changes. There was no difference between groups in the changes in FDP (mean difference, −11.7 μg mL −1 ; 95% CI, −32.9 to 9.5 μg mL −1 ; P = 0.28; I 2 = 32%).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow chart of study selection in the systematic review. We identified 12 articles (three RCTs and nine observational studies) in our systematic review (pooled sample size, 1409 patients; 838 in RCTs and 571 in observational studies) [14,23,[25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kudo et al. reported that serum concentrations of HMGB1 decreased within a couple of days after rTM administration in patients with sepsis‐induced DIC . We have also experienced cases in which an increase in HMGB1 was seen despite a chronological decrease in IL‐6 in patients who survived with combination therapy of PMX and rTM for septic shock complicated by DIC .…”
Section: Discussionmentioning
confidence: 87%